INFLUENCE OF SOME HERBS ON CONCENTRATION OF GLUCOSE IN HUMAN SERUM (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
In the current study the influence of water and ethanolic extracts of plants on the concentration of glucose in human serum has been investigated. Plants growing both on soil and hydroponic have been investigated. The results show that ethanolic extracts decrease glucose concentration in human serum more in comparison with water extracts. It can be observed that ethanolic extracts of soil herbs and hydroponic plants influence on glucose concentration in the same way. The studies have been carried out in human serum in vitro.
Keywords: herbs, soil, hydroponics, human serum, glucose concentration